Use of HCV+ Donors Does Not Affect HCV Clearance With Directly Acting Antiviral Therapy But Shortens the Wait Time to Kidney Transplantation. Issue 5 (May 2017) - Sawinski, Deirdre; Patel, Nikunjkumar; Appolo, Brenda; Bloom, Roy
Abstract : Background: Hepatitis C virus (HCV) infection is prevalent in the renal transplant population but direct acting antiviral agents (DAA) provide an effective cure of HCV infection without risk of allograft rejection. Methods: We report our experience treating 43 renal transplant recipients with 4 different DAA regimens. Results: One hundred percent achieved a sustained viral response by 12 weeks after therapy, and DAA regimens were well tolerated. Recipients transplanted with a HCV+ donor responded equally well to DAA therapy those transplanted with a kidney from an HCV− donor, but recipients of HCV+ organs experienced significantly shorter wait times to transplantation, 485 days (interquartile range, 228-783) versus 969 days (interquartile range, 452-2008; P = 0.02). Conclusions: On this basis, we advocate for a strategy of early posttransplant HCV eradication to facilitate use of HCV+ organs whenever possible. Additional studies are needed to identify the optimal DAA regimen for kidney transplant recipients, accounting for efficacy, timing relative to transplant, posttransplant clinical outcomes, and cost. Abstract : This small cohort study confirms the efficacy and tolerability of direct-acting antiviral agents for the treatment of Hepatitis C infection early after kidney transplantation, even in recipients of kidneys from Hepatitis C positive donors.